Características clínico-patológicas e prospecção das Ciclinas D1 e Ki-67 no diagnóstico e prognóstico de pacientes com câncer colorretal - Cândido, Inaldo dos Santos Casado (2023)
Colorectal cancer (CRC), currently, is classified as the third most incident cancer in the world. In addition, it ranks fourth among the neoplasms that cause more mortality on the planet. Cyclin D1 is a protein that acts in the regulation of the cell cycle, and currently has been pointed out as a possible diagnostic marker and prognosis for the treatment of certain types of cancer, including CRC. The Ki-67 protein is a well-known marker of cell proliferation, and some studies demonstrate that elevated Ki-67 expression can serve as a valuable predictive biomarker for poor prognosis in patients with CRC. The objective of this study was to evaluate the expression of Cyclin D1 and Ki-67 in samples of patients with colorectal cancer, by immunohistochemistry technique, and correlate to clinical-pathological data. The clinical data of 66 patients (> 18 years) diagnosed with CRC were collected (CAAE: 5,017,299) through the clinical records of Lauro Wanderley University Hospital and Napoleão Laureano Hospital, both in João Pessoa - PB. The paraffin blocks were obtained from the pathology laboratories of these hospitals and processed by immunohistochemistry with antibodies Anti-Cicline D1 and Anti-Ki-67. The slides were analyzed by optical microscopy and were categorized according to the markings: 0 (0%), 1 (≤10%), 2 (10-50%), 3 (50-80%) and 4 (> 80%). Expressions up to 10% (0 and 1) were considered negative and expressions above 10% (categories 2, 3 and 4) were considered positive. Information such as biological gender, age, color, schooling, location and size of the tumor, degree and histological type, metastasis in lymphatic organs and other organs, pathological staging and CEA marking of each patient were taken into account. Of the 66 patients involved in this study, 63.6% had positive expression for Cyclin D1. For Ki-67 protein, 65.2% of patients showed positive expression. There was a strong association between the positive expression of Cyclin D1 and Ki-67 (p=0.001). The present study found that most cases of CRC, included in this study, showed positivity for the expression of Cyclin D1 and Ki-67. However, there was no significant association between the expression of Cyclin D1 and Ki-67 with the variables taken into account in this study. The results shown in this study do not confirm Cyclin D1 and Ki-67 as markers that point to a good or bad prognosis. Further studies on the interference of molecular markers in clinical stages, such as diagnosis and prognosis, of patients with CRC are necessary.